MANAJEMEN KURIKULUM ADAPTIF: INTEGRASI PENDIDIKAN KARAKTER DAN DIGITALISASI PEMBELAJARAN - Hasbullah Hasbullah (CV. Adiba Aisha Amira, 2025)
This study aims to analyse the concept and strategy of character education integration and learning digitalisation within the framework of adaptive curriculum management. The transformation of digital technology has brought changes to the world of education, requiring a flexible curriculum that is able to adapt to the needs and characteristics of students. The integration of character education is very important in shaping a generation that is not only intellectually and digitally competent, but also has strong moral values. Through a systematic literature review, this study identifies the main challenges in implementation, such as the digital divide, low digital literacy, and lack of multi-stakeholder collaboration. The proposed strategies include strengthening digital literacy, teacher training, collaboration between schools, families, and communities, and developing project-based curricula that emphasise character values. The findings indicate that adaptive curriculum management with the integration of character education and digitalisation of learning can enhance the relevance, quality, and competitiveness of education in the global era. This study recommends the need for educational policies that support curriculum innovation, improve educator competencies, and ensure equitable access to technology to create inclusive and sustainable education.